Positive and Negative Politeness in Refusals in Three American Drama Movies - Arie Charismawati (Lexicon, 2013)
This research paper attempts to investigate positive and negative politeness of refusal in three American drama movies. In particular, it attempts to identify and classify the positive and negative politeness strategies used to express refusal in the movies. The data used in this research were dialogues containing refusal expressed by the use  of positive and negative politeness strategies proposed by Brown and Levinson (1987). Based on the data analysis, 73 refusal utterances were found: 31 utterances (42.5%) were found in Legally Blonde, 22 utterances (30.1%) in Yes Man, and 20 utterances (27.4%) in He’s Not That Just into You. From 73 refusals found, out of 32 (43.8%) were expressed using positive politeness strategy, and remaining 41 (56.2%) refusals were expressed using negative politeness strategy. It was found in this research that positive politeness strategy 13 give (or ask for) reason is considered as the most commonly used positive politeness strategy in the movies.  This strategy was used 7 times (21.8%). Meanwhile, in negative politeness strategy, strategy 1 be conventionally indirect appears as the most frequently strategy used in giving refusal in the movies. This strategy was used 18 times (43.9%).